2012
DOI: 10.1371/journal.pone.0046001
|View full text |Cite
|
Sign up to set email alerts
|

MAML1 Acts Cooperatively with EGR1 to Activate EGR1-Regulated Promoters: Implications for Nephrogenesis and the Development of Renal Cancer

Abstract: Mastermind-like 1 (MAML1) is a transcriptional coregulator of activators in various signaling pathways, such as Notch, p53, myocyte enhancer factor 2C (MEF2C) and beta-catenin. In earlier studies, we demonstrated that MAML1 enhanced p300 acetyltransferase activity, which increased the acetylation of Notch by p300. In this study, we show that MAML1 strongly induced acetylation of the transcription factor early growth response-1 (EGR1) by p300, and increased EGR1 protein expression in embryonic kidney cells. EGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…In Paper II we suggested a possibility of arsenic been effective against renal cancers overexpressing MAML1 protein. An in silico study has showed that MAML1 expression was increased in renal cancer cell carcinoma and that it correlated with decreased patients' survival (Hansson et al 2012). In this respect, treatment of renal tumor cells overexpressing MAML1 with arsenic could possibly downregulate the levels of MAML1 and decrease cell proliferation, as was reported for HEK293 cells in Paper II.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In Paper II we suggested a possibility of arsenic been effective against renal cancers overexpressing MAML1 protein. An in silico study has showed that MAML1 expression was increased in renal cancer cell carcinoma and that it correlated with decreased patients' survival (Hansson et al 2012). In this respect, treatment of renal tumor cells overexpressing MAML1 with arsenic could possibly downregulate the levels of MAML1 and decrease cell proliferation, as was reported for HEK293 cells in Paper II.…”
Section: Discussionmentioning
confidence: 61%
“…In the absence of a Wnt signal, the cytoplasmic β-catenin is continuously degraded by the Axis complex (MacDonald, Tamai, and He 2009). Once a Wnt ligand binds to the Frizzled (Fz) receptor, which is a transmembrane protein, and its co-receptor LRP6 protein, the Axis complex is recruited to the reported that MAML1 and KAT2B copy number variances were predominant changes in patients with clear-cell renal cell carcinoma (ccRCC) (Hansson et al 2012;Feng et al 2015).…”
Section: Mastermind-like 1 Protein (Maml1)mentioning
confidence: 99%
See 1 more Smart Citation
“…It could enhance the acetyltransferase activity of p300 and in turn promoted the acetylation of Notch [27]. Also, MAML1 could induce acetylation of the transcription factor early growth response-1 (EGR1) by p300 in embryonic kidney cells [28]. Those results together with that Notch was Network analysis of the Notch gene set in clear cell renal cell carcinoma (ccRCC).…”
Section: Discussionmentioning
confidence: 95%
“…This exciting finding suggests that EMT and MET are not mutually exclusive, and that WT1 could be an important modulator of the equilibrium between the two states. Interestingly Orai1 expression has been shown to be associated with favorable prognosis in clear cell RCC where genetic and epigenetic alterations in EGR1 expression were associated with survival [126, 127]. However, the extent to which EGR1/WT1-mediated regulation of Ca 2+ signaling components contributes to EMT/MET transitions remains unknown.…”
Section: Dysregulation Of Soce In Cancermentioning
confidence: 99%